Patterns of phonosemantic reduplication in Kartvelian (South Caucasian) languages - Zaal Kikvidze; Rusudan Gersamia; Maia Lomia (LingBaW)
In terms of phonosemantic doubling, root reduplication (in combination with affixation) is the most productive technique in Kartvelian languages (Georgian, Megrelian, Laz, Svan). The paper is a description of patterns of Kartvelian phonosemantic reduplication with respect to their both morphological and phonological parameters. The following types have been identified: 1. Root reduplication; 2. Syllable reduplication; 3. Redupluication with affixation. Each type has its respective sub-types. Based on abounding empirical data, the paper is an attempt to scrutinize and detect whether and how the above mentioned patterns are valid for all the four Kartvelian languages and to draw inferences about occurring formal and/or functional regularities associated with phonosemantic reduplication.